1999
DOI: 10.1056/nejm199911113412003
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison of Virtual and Conventional Colonoscopy for the Detection of Colorectal Polyps

Abstract: In a group of patients at high risk for colorectal neoplasia, virtual and conventional colonoscopy had similar efficacy for the detection of polyps that were 6 mm or more in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
252
6
16

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 687 publications
(285 citation statements)
references
References 44 publications
9
252
6
16
Order By: Relevance
“…Computed tomographic colonography (CTC) is increasingly used as a relatively non-invasive method of colonic investigation both for colorectal cancer (CRC) screening [1][2][3] and for patients with symptoms suggestive of CRC [4][5][6][7]. Data from large studies on screening cohorts have suggested that CTC and conventional colonoscopy have similar sensitivity for polyps ≥6-mm in diameter [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomographic colonography (CTC) is increasingly used as a relatively non-invasive method of colonic investigation both for colorectal cancer (CRC) screening [1][2][3] and for patients with symptoms suggestive of CRC [4][5][6][7]. Data from large studies on screening cohorts have suggested that CTC and conventional colonoscopy have similar sensitivity for polyps ≥6-mm in diameter [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cross sectional imaging techniques including magnetic resonance imaging (MRI) and computed tomography (CT) are increasingly being considered as alternative imaging modalities for colorectal screening [1,2]. Using thin section axial images and assigned software both techniques allow the generation of three-dimensional views of the colon, simulating those obtained with conventional colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study comparing single-slice CT colonography and conventional colonoscopy suggests similar efficacy Colorectal polyps: Detection with multi-slice CT colonography for detection of polyps 6 mm or more in diameter (82 ± 91 %). However, restrictions in spatial resolution resulted in a low sensitivity for polyps smaller 6 mm (55 %) and frequent false positive findings [1].…”
Section: Introductionmentioning
confidence: 99%
“…Key words: Magnetic resonance imaging (MRI) ± Virtual endoscopy ± Colon ± Contrast medias highly sensitive for detecting colorectal polyps exceeding 8 mm in size [5,6]. Despite high diagnostic accuracy, the considerable exposure to ionising radiation casts a shadow over the future of CT colonography as a screening exam for colorectal cancer [7].…”
Section: Discussionmentioning
confidence: 99%